2010
DOI: 10.1375/twin.13.5.437
|View full text |Cite
|
Sign up to set email alerts
|

Are There Sex Differences in the Genetic and Environmental Effects on Mental Rotation Ability?

Abstract: Probably the most robust sex difference in cognitive abilities is that on average males outperform females in tests of mental rotation. Using twin data we tested whether there are sex differences in the magnitude of genetic and environmental effects on mental rotation test performance and whether the same or different genetic effects operate in females and males. The present study replicated the well-known male advantage in mental rotation ability. The relative proportion of variance explained by genetic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The results of this study are somewhat consistent with those of Vuoksimaa et al (2010). Although the latter study examined a Finnish sample and we examined a Japanese sample, the best-fitting model for both populations was the AE model.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of this study are somewhat consistent with those of Vuoksimaa et al (2010). Although the latter study examined a Finnish sample and we examined a Japanese sample, the best-fitting model for both populations was the AE model.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, no quantitative sex differences in the unique environmental influence on mental rotation ability were observed in this study. In contrast to the current and Finnish (Vuoksimaa et al, 2010) results yielded from genetic analysis, several studies have reported that family and social factors affect the impact of sex on mental rotation ability (Levine et al, 2005;Lippa et al, 2010;Silverman et al, 2007). The divergent results may indicate a gene-environment correlation (Rutter, 2006): the genetic contribution to mental rotation ability may be mediated by family and social factors.…”
Section: Discussionmentioning
confidence: 72%
“…To date, behavioral genetic studies have only found small 32 , or non-existent 33 , sex differences in etiology of any cognitive abilities. In line with this, studies on the etiology of spatial ability found only negligible differences in genetic and environmental factors driving sex differences in spatial ability in males and females 19 , including in mental rotation 28 .…”
Section: Introductionmentioning
confidence: 67%
“…Both biological and environmental factors have been proposed to initiate and maintain the sex differences in spatial ability. Environmental explanations have highlighted the role of previous experiences and learning environments 26 , 27 , whereas biological investigations have concentrated on genetic and hormonal effects 28 31 . To date, behavioral genetic studies have only found small 32 , or non-existent 33 , sex differences in etiology of any cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…The examination of differences in human cognitive functioning through the exploration of abilities such as spatial visualization (Halpern, 2000;Hyde, 2005) that involves using tasks associated with spatiotemporal ability (e.g., De Goede & Postma, 2008;Vuoksimaa, et al, 2010) constitutes an area of continuing research interest. Halpern (2000) defi ned this type of visual-spatial ability as cognitive processing involving "judgments about and responses to dynamic (i.e., moving) visual displays" (p. 101).…”
Section: Introductionmentioning
confidence: 99%